Measuring depth of relationships using subconstructs of trust and commitment: an empirical study in retail banking - Asaithambi, Govinda (2004)
Customer retention has become the mantra of the business world. Companies are implementing relationship marketing tools with the conviction that these would yield great profits by retaining customers. But the abject reality is that the most of the customer relationship management initiatives are glorified failures. This makes it necessary for us to go the drawing board and ask fundamental question regarding customer firm relationships. does the customer really want to have a relationship with the firm if the customer does want a relationship, then what is the level of relationship that can exist or that exist between the customer and the firm? i have tried to the address the later question of the level of relationship by attempting to measure the depth of the customer firm relationship